- PENGARUH PENGGUNAAN MEDIA PHET COLORADO TERHADAP PEMAHAMAN KONSEP PECAHAN SISWA KELAS V SDN 25 MATTIROWALIE KABUPATEN BONE: - - -, Sudirman; Rosmalah; Farah Ainun Nisa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Understanding of Mathematical concepts among elementary school students remains relatively low due to the abstract nature of the material, particularly regarding fractions. This study aims to determine the effect of using the PhET Colorado software on the understanding of fraction concepts among fifth-grade students at SDN 25 Mattirowalie. This study employs a quantitative, pre-experimental approach with a One-Group pre-test-post-test design. The sample in this study consisted of 30 fifth-grade students at SDN 25 Mattirowalie, selected using a saturation sampling technique. Data collection was conducted using a multiple-choice test. Data analysis employed descriptive statistical analysis and inferential statistical analysis using the Paired Sample t-Test. Based on the results of the descriptive analysis, it was found that: (1) the pre-test mean score of 53.40 fell into the “below average” category, while the post-test mean score of 82.23 falls into the good category; (2) the results of the inferential statistical analysis show a significance value of 0.001 < 0.05, and a calculated t-value of 22.302 > 2.094 (table t-value). Thus, the use of the PhET Colorado media has a significant effect on the understanding of fraction concepts among students in Grade 5 at SDN 25 Mattirowalie.